THE EFFECT OF ASSETS STRUCTURE AND FIRM SIZE ON FIRM VALUE MEDIATED BY CAPITAL STRUCTURE - Eka Wulan Sari; Elly Siswanto (University of Science and Computer Technology, 2022)
This paper aims to investigate how the effect of Assets Structure and Firm Size on Firm Value Mediated by CapitalStructure in Non-Financial Sector Companies Listed on the Indonesia Stock Exchange period 2013-2021. Theresearch method used in this research quantitative An empirical research was conducted with a quantitativeapproach using panel regression OLS to estimates the dirrect effect and Partial Least Squares Structural EquationModeling (PLS-SEM) to estimates indirect effect, by using STATA statistical software. sample selection usingpurposive sampling and found a sample of 180 companies. From the analysis it was found that capital structureand asset structure have no effect on firm value, Firm size has a negative significant on firm value , asset structurehas a negative significant on capital structure, firm size has a positive significant effect on capital structure. Inaddition, capital structure is able to mediate the relationship between asset structure and firm size on firm value.Empirical studies conducted usually only look at the direct effect of the independent variable on the dependentvariable, but in this study examines the direct and indirect effects of the independent variables on the dependentvariable. In addition, this study does not only use samples from 1 company sector, but using all non-financialsectors companies listed on the Indonesia Stock Exchange.